2010
DOI: 10.1002/jctb.2555
|View full text |Cite
|
Sign up to set email alerts
|

Manufacture of fibrous reinforcements for biodegradable biocomposites from Citysus scoparius

Abstract: BACKGROUND: Cytisus scoparius samples were processed with hot, compressed water (autohydrolysis treatments) to obtain both fiber-containing solids (suitable as reinforcements for composites) and a liquid phase containing sugar oligomers derived from hemicelluloses. The solid phase from autohydrolysis, mainly made up of cellulose and lignin, was employed for manufacturing polylactic acid (PLA)-based biodegradable composites. The mechanical properties, water uptake and thermal properties of composites were asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 27 publications
2
19
0
Order By: Relevance
“…Autohydrolysis processing of broom branches with hot compressed water has been proposed to produce a solid‐containing fraction mainly made up of cellulose and lignin and a liquid phase containing sugar oligomers derived from hemicelluloses. The solid phase was used for manufacturing polylactic acid based biodegradable composites, and the sugar oligomers in the soluble fraction could be suitable as prebiotic agents . However, in this soluble phase a phenolic fraction is also present.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Autohydrolysis processing of broom branches with hot compressed water has been proposed to produce a solid‐containing fraction mainly made up of cellulose and lignin and a liquid phase containing sugar oligomers derived from hemicelluloses. The solid phase was used for manufacturing polylactic acid based biodegradable composites, and the sugar oligomers in the soluble fraction could be suitable as prebiotic agents . However, in this soluble phase a phenolic fraction is also present.…”
Section: Introductionmentioning
confidence: 78%
“…Cellulose (27.3–28.5%) was the major structural fraction, followed by acid insoluble lignin (19.3–22.8%) and hemicelluloses (15.5–16.7%), which were mainly constituted of xylan, araban and acetyl groups. The hemicelluloses and Klason lignin contents were in the range reported for broom samples collected in Ourense (Spain), but significantly lower cellulose content was determined . Ammar et al found that compared with stems, leaves had a high nutritive value and were less affected by seasonal variations.…”
Section: Resultsmentioning
confidence: 99%
“…Young's modules of reinforced composites increase with respect to the neat PLA (PLA1 for ABF and ACW, and PLA2 for AEW and ARH) by 41-74%. Lower values for Young's modules (2.96 and 2.84 GPa for ABF and ACW, respectively) were achieved when the percentage of reinforced materials was 20 (Gonza´-lez, Campos, Cunha, Santos, & Parajo´, 2011;. Tensile strength presents a slight decrease in the reinforced composites except in the samples carried out with AEW.…”
Section: Cellulose and Lignin-enriched Solid For Biocomposites' Manufmentioning
confidence: 90%
“…This reduction in water absorption is ascribed to the selective removal of the more hydrophilic hemicelluloses and increase of lignin in the residual fibers. Higher percentages of reinforced fibers increased the water absorption (Gonza´lez, Campos, et al, 2011;.…”
Section: Cellulose and Lignin-enriched Solid For Biocomposites' Manufmentioning
confidence: 92%
See 1 more Smart Citation